2006
DOI: 10.1089/hum.2006.17.845
|View full text |Cite
|
Sign up to set email alerts
|

Safety in Nonhuman Primates of Ocular AAV2-RPE65, a Candidate Treatment for Blindness in Leber Congenital Amaurosis

Abstract: Leber congenital amaurosis (LCA) is a molecularly heterogeneous disease group that leads to blindness. LCA caused by RPE65 mutations has been studied in animal models and vision has been restored by subretinal delivery of AAV-RPE65 vector. Human ocular gene transfer trials are being considered. Our safety studies of subretinal AAV-2/2. RPE65 in RPE65 -mutant dogs showed evidence of modest photoreceptor loss in the injection region in some animals at higher vector doses. We now test the hypothesis that there ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 42 publications
6
78
0
2
Order By: Relevance
“…Large animal studies to date, including primate safety studies, have mainly treated the area centralis or central retinal region (14,(41)(42)(43), so this region is a likely target for subretinal gene therapy. Thus, our finding of early foveal cone loss has strong clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Large animal studies to date, including primate safety studies, have mainly treated the area centralis or central retinal region (14,(41)(42)(43), so this region is a likely target for subretinal gene therapy. Thus, our finding of early foveal cone loss has strong clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies of these products generally focus on the safety and tolerability of the cells, rather than the procedure 38,39 ; furthermore, preclinical studies of subretinal cell delivery have reported the occurrence of retinal perforations and hemorrhages, though not generally the rates of these complications. [39][40][41] These findings highlight the need for a procedure and device with improved safety outcomes for subretinal delivery of therapeutic products.…”
Section: Discussionmentioning
confidence: 99%
“…They did not detect vector DNA in a dose escalation study of subretinally injected AAV2/2 in dogs (Jacobson et al 2006a), but temporarily detected it in the optic nerve and brain of primates 1 week after the animals received a subretinal injection of AAV2/2 vector (Jacobson et al 2006b). At 3 months after injection, only one primate had a detectable number of copies in the left geniculate nucleus.…”
Section: Safety and Biodistribution Of Raav-mediated Gene Transfermentioning
confidence: 97%